Concepções evolutivas de Charles Darwin na Origem das espécies (1859) e na Expressão das emoções no homem e nos animais (1872): um estudo comparativo - Castilho, Fernando Moreno (2010)
Among the books written by Charles Robert Darwin (1809-1882) the Origin of species (1859) is the best known. However, in such book he did not deal with man. He had dealt with this subject in two books which were published later: The expression of emotions in man and animals (1872) and The descent of man (1871). This dissertation aims to elucidate if Darwin had presented the same ways of modification of the species in The origin of species and The expression of emotions in man and animals. It will be also taken into account some conceptions presented by him in The descent of man. This study contains an introduction and three chapters. Chapter 1 deals with some of Darwin s contributions offering an overview of the main ways of modification found in the Origin of species. Chapter 2 analyses the ways of modification of species found in The expression of emotions in man and animals. Chapter 3 offers a comparison between the conceptions found in both books as well as providing some final remarks on the subject. This study led to the conclusion that the ways of modification of species proposed in both books are the same: natural selection, sexual selection, inheritance of acquired characteristics. Besides that, it may be found an analogy between natural and artificial selection in both of them. However, in The expression of emotions in man and animals Darwin stressed the role of the inheritance of acquired characteristics in order to explain some patterns of behaviour in man and other animals. It can also be pointed out that several conceptions found in The Expression had inspired some more recent works contributing for the building of the discipline Ethology, in the 1960 s